2019
DOI: 10.1371/journal.pone.0218182
|View full text |Cite
|
Sign up to set email alerts
|

Validating a dimension of doubt in decision-making: A proposed endophenotype for obsessive-compulsive disorder

Abstract: Doubt is subjective uncertainty about one’s perceptions and recall. It can impair decision-making and is a prominent feature of obsessive-compulsive disorder (OCD). We propose that evaluation of doubt during decision-making provides a useful endophenotype with which to study the underlying pathophysiology of OCD and potentially other psychopathologies. For the current study, we developed a new instrument, the Doubt Questionnaire, to clinically assess doubt. The random dot motion task was used to measure reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 30 publications
7
25
1
Order By: Relevance
“…The drift-diffusion model has been studied in a wide range of contexts and domains including the dot motion task and has converging support from both behavioral and neural data (13,15,17,(28)(29)(30). Previous work has shown specifically that drift rate is impaired (reduced) both in patients with OCD and in subclinical individuals with high levels of self-reported OCD symptoms (21)(22)(23)(24). Moreover, impairments are larger for easier decisions (21,24).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The drift-diffusion model has been studied in a wide range of contexts and domains including the dot motion task and has converging support from both behavioral and neural data (13,15,17,(28)(29)(30). Previous work has shown specifically that drift rate is impaired (reduced) both in patients with OCD and in subclinical individuals with high levels of self-reported OCD symptoms (21)(22)(23)(24). Moreover, impairments are larger for easier decisions (21,24).…”
Section: Significancementioning
confidence: 99%
“…This also aligned within a more general goal we had for developing a paradigm that was complex enough to ask a wide array of questions about continued deliberation across decisions but simple enough to reliably model and recover parameter values at the individual subject level without onerously long testing sessions. Finally, numerous studies have documented impairments within single decision episodes in this task both in patients with OCD and in subclinical individuals high on the OCD spectrum (21)(22)(23)(24) (but see also ref. 25), making it an obvious choice for extending the investigation of individual differences across repeated decision episodes.…”
Section: Significancementioning
confidence: 99%
“…Additionally, decision-making deficits seen in OCD can be related to pathological doubt, a common phenomenon seen in OCD. Studies have shown that patients with OCD often experience uncertainty when making decisions due to a lack of confidence in their own perception, attention, and memory (77)(78)(79). In decision-making tasks, this can manifest as longer response times compared to healthy controls (77).…”
Section: Striatum In Ocdmentioning
confidence: 99%
“…', or 'Should I go to the pub at the end of lockdown?' Obsessive-compulsive disorder (OCD) [1][2][3] has been postulated to be characterized by impairments in doubt, potentially triggering pathological symptoms such as checking or washing, which, following the execution of repeated actions [4][5][6] further increases the doubt 1 .…”
Section: Introductionmentioning
confidence: 99%
“…But computational parameters estimated using a hierarchical drift-diffusion model (HDDM) showed an increase in the threshold parameter (which indicates the amount of evidence accumulated before a choice is selected) in OCD patients when the randomness of the dots increased 9 . OCD patients with higher doubt scores had low drift rates and lower certainty in their decisions 2 . Hauser and colleagues show increased thresholds 22,23 and decreased drift rates along with meta-cognitive deficits in individuals with higher compulsive traits 24 .…”
Section: Introductionmentioning
confidence: 99%